Agrobiodiversidade e produtividade agrícola de um Sistema Agroflorestal em uma Comunidade que Sustenta a Agricultura: uma ilha de possibilidades em meio à agricultura convencional. - Lima, Gabriel Rodrigues (2023)
In this dissertation, the main objective is to quantify and analyze the agricultural production of the productive unit that integrates a Community Supported Agriculture (CSA), which practices and promotes agroecology and uses agroforestry management in the municipality of Guapiaçu, São Paulo (SP), Brazil. Throughout the research, the results demonstrated that agroecology guidelines have a fundamental role in orientating CSA activities, which results in a diversified agroecosystem that boosts significant productivity in relation to the area used for planting. With the adoption of agroecological practices such as integrated management, the valorization of agrobiodiversity and the cultivation of Non-Conventional Food Plants (PANCs, in Portuguese abbreviation), CSA obtained significant results in terms of productivity and agricultural diversity. Varied crops and the integration of perennial elements, such as fruit trees and shrubs, have led to increased productivity in the system, while strengthening the resilience of the agroecosystem in the face of environmental and climatic challenges. The data revealed that CSA achieved an average monthly productivity of 324.25 kilos of food throughout the year, with emphasis on October, in which 449 kilos and 38 different species were produced. This significant heterogeneity of food crops stands out compared to the global average, based in only 20 products grown in monocultures. The presence of 97 species throughout the year highlights the indispensability of the agroecosystem in promoting agrobiodiversity, which increases the possibilities of food choice and differentiates itself from the conventional agricultural production market. In addition to the quantitative results, the study highlighted the importance of social and cultural interactions promoted by CSA, and the cultivation of PANCs boosted diversity and enriched the system – this aspect not only impacts the food security of the communities involved, but also values social ties and local traditions. In conclusion, agroecology and agroforestry management are reinforced as essential aspects for the development of regenerative, biodiverse and productive agroecosystems in a long term. The agroecological approach adopted by CSA not only produces clean and healthy food, but also creates a food culture based on environmental and social responsibility, which positively affects the achievement of Sustainable Development Goals (SDGs) in Brazil.